Evaluasi Prasyarat Keberhasilan Sistem Resi Gudang di Kabupaten Bantul - Achmad Fachruddin; Lestari Rahayu (AGRARIS: Journal of Agribusiness and Rural Development Research, 2017)
During 2011-2016, there was a decreasing trend of warehouse receipt sistem (WRS) transactions in Bantul regency and the participants of the WRS came from a small part of the districts.  This condition indicated that there was an unfulfilled  prerequisites for success of the WRS.  This study aims to identify the role of stakeholders in the implementation of WRS and evaluate the prerequisites for success of WRS in Bantul regency. The research was conducted by in-depth interviews to stakeholders of the WRS. Data analysis was done using descriptive method. The result showed that stakeholders that have a big role in increasing warehouse receipts transactions were warehouse manager and department of trade. The increasing of production was a prerequisite that reinforces the existence of WRS in Bantul regency.  The success of the WRS were depends on two prerequisite of the commitment of local government and education and socialization to farmers. These findings indicate the need for the local governments to supports programs related to WRS and to intensify the dissemination of WRS to farmers in potential villages.